IMPLEMENTASI NILAI SIPAKATAU DAN SIPAKALEBBI DI UPTD SMP NEGERI 9 PAREPARE DALAM MENGELOLA ORGANISASI MENYONGSONG ERA 5.0 - Ayu Darapati, Andi Putri; Mandasari, Sri Dwi; Imran Arif, Muhammad; Alwi, Muhammad (IAIN Parepare, 2025)
This study aims to determine the implementation of sipakatau and sipakalebbi values in UPTD SMP Negeri 9 Parepare in managing the organization to welcome era 5.0 and how the leadership and role of the principal and all stakeholders in UPTD SMP Negeri 9 Parepare in managing the organization, and what are the solutions given to overcome the problem of the waning of sipakatau and sipakalebbi values in managing the organization at the UPTD of SMP Negeri 9 Parepare. Sipakatau humanizes each other and sipakalebbi respects each other. This study uses a qualitative approach with descriptive methods, descriptive methods in this study with the aim of describing the implementation of sipakatau and sipakalebbi values at UPTD SMP Negeri 9 Parepare in managing organizations to meet Era 5.0. The data sources in this study were conducted by means of observation, interviews, and documentation. The results showed that the implementation of sipakatau and sipakalebbi values in organizational management had long been applied in UPTD SMP Negeri 9 Parepare in improving the performance of all stakeholders and principals as leaders in carrying out their duties and functions in accordance with the application of sipakatau and sipakalebbi culture in their management.